Strategi KPU Kabupaten Sleman dalam Pelaksanaan Pemilihan Kepala Daerah di Daerah Kawasan Rawan Bencana Erupsi Gunung Merapi Tahun 2020 - Arisonatalia, Proventy; Tjahjoko, Guno Tri (Indonesian Journal Publisher, 2022)
The General Election Commission (KPU) of Sleman Regency as an election organizer at the district level is quite legitimately given the authority by law to hold the election of the Regent and Deputy Regent and/or Mayor and Deputy Mayor. In the dynamics of holding the 2020 Simultaneous Elections, the experience of the Sleman Regency KPU is quite unique. Its uniqueness lies in its implementation element, which coincides with the non-natural Covid-19 disaster as well as the threat of a natural disaster from the eruption of Mount Merapi, which at that time was on alert level III, exactly one month before the D Day of the voting. Of course, it will affect the implementation of the Simultaneous Election stages in 2020. What is the strategy of the Sleman Regency KPU in dealing with simultaneous elections in areas prone to the eruption of Mount Merapi, because the impact will affect the level of community participation? Using descriptive qualitative research, namely research that is intended to provide data as accurate as possible about humans, circumstances, or other symptoms. The author identifies that the implementation of the 2020 simultaneous elections in Sleman Regency can run well and the level of voter participation in the refugee areas is quite high, because the Sleman Regency KPU has mapped areas that are potentially affected by disasters, then coordinated communication and consolidation with stakeholders intensively resulted in policies that were effective. least risk. Consultation with the highest policy makers, namely the RI KPU as the basis for the Sleman Regency KPU to make decisions regarding the shifting of TPS. Build trust with election organizers, especially ad hoc bodies, so that the power of one command can be established, so that the implementation of the elections runs smoothly, and synergize with relevant stakeholders outside the stages, in order to facilitate coordination when the election stages will take place.